A comparison between left ventricular ejection time measurement methods during physiological changes induced by simulated microgravity. Issue 3 (24th January 2022) - Orter, Stefan; Möstl, Stefan; Bachler, Martin; Hoffmann, Fabian; Mayer, Christopher C.; Kaniusas, Eugenijus; Reisinger, Michaela; Wassertheurer, Siegfried; Tank, Jens; Jordan, Jens; Hametner, Bernhard
Abstract : New Findings: What is the central question of this study? First, we validated easy‐to‐use oscillometric left ventricular ejection time (LVET) against echocardiographic LVET. Second, we investigated progression of left ventricular ejection time index (LVETI), pre‐ejection period index (PEPI), total electromechanical systole index (QS2I) and PEP/LVET ratio during 60 days of head‐down tilt (HDT). What is the main finding and its importance? The LVETosci and LVETecho showed good agreement in effect direction. Hence, LVETosci might be useful to evaluate cardiovascular responses during space flight. Moreover, the approach might be useful for individual follow‐up of patients with altered ejection times. Furthermore, significant effects of 60 days of HDT were captured by measurements of LVETI, PEPI, QS2I and PEP/LVET ratio. Abstract: Systolic time intervals that are easy to detect might be used as parameters reflecting cardiovascular deconditioning. We compared left ventricular ejection time (LVET) measured via ultrasound Doppler on the left ventricular outflow tract with oscillometrically measured LVET, measured at the brachialis. Furthermore, we assessed the progression of the left ventricular ejection time index (LVETI), the pre‐ejection period index (PEPI), the Weissler index (PEP/LVET) and the total electromechanical systole index (QS2I) during prolonged strict head‐down tilt (HDT) bed rest, including 16 male and eight female subjects. Simultaneous oscillometric and echocardiographic LVET measurements showed significant correlation ( r  = 0.53 with P  = 0.0084 before bed rest and r  = 0.73 with P  < 0.05 on the last day of bed rest). The shortening of LVET during HDT bed rest measured with both approaches was highly concordant in their effect direction, with a concordance rate of 0.96. Our results also demonstrated a significant decrease of LVETI ( P  < 0.0001) and QS2I ( P  = 0.0992) and a prolongation of PEPI ( P  = 0.0049) and PEP/LVET ( P  = 0.0003) during HDT bed rest over 60 days. Four days after bed rest, LVETI recovered completely to its baseline value. Owing to the relationship between shortening of LVETI and heart failure progression, the easy‐to‐use oscillometric method might not only be a useful way to evaluate the cardiovascular system during space flights, but could also be of high value in a clinical setting.